More Than Just Periods: Understanding the role of communication and advertising in shaping and challenging menstrual stigmas in Urban India - Sen,Aditya Sandeep (2025)
This thesis critically analyzes the stigmatization of menstrual experiences by identifying societal factors, communication channels, and communication norms, with a focus on understanding the power and effects of advertising narratives on menstrual stigmas. This thesis aims at recognizing the importance of menstrual justice, by framing menstrual experiences as human rights. This helps us recognize menstrual injustices that cause discrimination and concealment through societal factors and their communication. This research project engages with societal factors like gender, class, culture, religious background age that contribute to shaping stigmas within menstrual experiences. By engaging with these societal factors, this study focuses on understanding how these communication norms shape menstrual stigmas by identifying them. The research was designed around 10 interviews of Indian Urban Class Women, as this aligned with accessibility to participants by virtue of my position. The interview consisted of open-ended questions exploring menstrual stigmas to identify societal factors. This approach helped identify how menstrual stigmas are seen in practices of religion, caste, class, and so on. These practices are connected through attitudes of patriarchal norms. This attitude is also reflected and reinforced in communication norms through various channels. Through the interviews, we also identify that media narratives such as advertising hold the power to reflect and dictate menstrual stigmas and it mostly does it through concealment and misinformation. This misinformation has various consequences, especially for women at a young age. By furthering our understanding of media technologies, we see how menstruation is having its moment through digitalization, where feminist discourses that advocate for agency, gender equity, and body representation shine bright. By riding this wave, advertising narratives can benefit from promoting menstrual justice through lived experiences and expose menstrual stigmas through an empathetic lens. This empathy is identified by various interviewees as the communication style through which they communicate with women and individuals whom they are comfortable with with respect to their menstrual experiences. By listening, understanding, and amplifying this community bond that women share with each other, brands can create a strong brand image while tackling menstrual stigmas.